Determinants of Financial Management Behavior of Millennial Generation in Surabaya - Ramadhan, Aditya Yanuar; Asandimitra, Nadia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
The habit of millennial generations in Surabaya in conducting online shopping activities can influence their financial management behavior. This study aims to investigate the factors that can affect financial management behavior with a sample of 184 millennial generations in Surabaya using multiple linear regressions. The findings demonstrated that financial attitude, financial knowledge, and secondary agents had a positive effect on financial management behavior. Whereas locus of control, childhood consumer experience, and primary agent did not affect on financial management behavior. Millennial generations in Surabaya have financial attitudes and knowledge, while also supported by adequate digital and internet literation.